2014
DOI: 10.1177/0192623314522885
|View full text |Cite
|
Sign up to set email alerts
|

The Role of eNOS Phosphorylation in Causing Drug-induced Vascular Injury

Abstract: Previously we found that regulation of eNOS is an important part of the pathogenic process of Drug-induced vascular injury (DIVI) for PDE4i. The aims of the current study were to examine the phosphorylation of eNOS in mesentery versus aorta at known regulatory sites across DIVIinducing drug classes and to compare changes across species. We found that phosphorylation at S615 in rats was elevated 35-fold 2 hr after the last dose of CI-1044 in mesentery versus 3-fold in aorta. Immunoprecipitation studies revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Single‐dose rat study (150 μg/kg) revealed myocardial necrosis with several foci together with perivascular and ventricular oedema, whereas during repeated dose study (30 μg/kg per 4 days) fibrotic heart tissue has developed . Mechanisms of cardiovascular toxicity still remain uncertain but appear to be partly related to excessive induction of endothelial nitric oxide synthase . It was also suggested from multiple sources that some antidepressants (citalopram, amitriptyline) may cause QRS/QT prolongation activating A 1 AdRs.…”
Section: Organ‐specific Toxicity Of Adenosine Derivatives and Adenosimentioning
confidence: 99%
See 1 more Smart Citation
“…Single‐dose rat study (150 μg/kg) revealed myocardial necrosis with several foci together with perivascular and ventricular oedema, whereas during repeated dose study (30 μg/kg per 4 days) fibrotic heart tissue has developed . Mechanisms of cardiovascular toxicity still remain uncertain but appear to be partly related to excessive induction of endothelial nitric oxide synthase . It was also suggested from multiple sources that some antidepressants (citalopram, amitriptyline) may cause QRS/QT prolongation activating A 1 AdRs.…”
Section: Organ‐specific Toxicity Of Adenosine Derivatives and Adenosimentioning
confidence: 99%
“…[119] Mechanisms of cardiovascular toxicity still remain uncertain but appear to be partly related to excessive induction of endothelial nitric oxide synthase. [120] It was also suggested from multiple sources that some antidepressants (citalopram, amitriptyline) may cause QRS/QT prolongation activating A 1 AdRs. Cardiovascular toxicity was reversed, when AdR antagonists were employed.…”
Section: Cardiovascular Toxicitymentioning
confidence: 99%
“…Serum nitrite: The measurement of serum nitrite was performed using the total nitric oxide (NO) assay (R&D Systems, Minneapolis, Minnesota, USA) according to the manufacturer's instructions. The (30), and high-Danshen group (30). Each group mice has three endings: A, B, and C. The A ending: mice were intravenously administered Danshen or saline five times, at 0, 24, 48, 72, and 96 h respectively.…”
Section: Detection Of Serum No and Et-1mentioning
confidence: 99%
“…A unifying feature in common with these proposed mechanisms is the observation of high production of NO within tissues after exposure to many compounds producing vascular effects. Many drugs also have signaling pathways that can pass through endothelial nitric oxide synthase (eNOS), and modulation of NO production can affect lesion severity (Tobin et al 2014).…”
Section: Preclinical Divi Associated With Small Moleculesmentioning
confidence: 99%